Aplikasi Pengolahan Data Kelahiran, Kematian, Datang dan Pindah Menggunakan Bahasa Pemrograman PHP - Zalmadani, Hendro; Hartomi, Zupri Henra (SAFE-Network, 2025)
Padang Birik-Birik Village is one of the villages in North Pariaman District, Pariaman City. The process of recapitulating birth, death, arrival, and moving letters received at the Padang Birik-Birik Village Office has problems, namely the process of making a cover letter for birth certificates and death certificates as well as arrival and moving letters. For the cover letter for birth certificates, it is done by filling out form F-2.09, for the cover letter for death certificates, it is done by filling out form F-2.20, to make a cover letter for arrival, it is done by filling out form F-1.01, Furthermore, for and moving letters, it is also done by filling out form F-1.04 which is done by hand. Another problem is the difficulty of finding archives/files of population data in the filing cabinets that are piled up and so many, because the process of finding archives/data files is done conventionally, namely looking at documents one by one. In developing the system, the author uses the waterfall method where the data collection techniques used include observation and interviews. For the development method using a structured method with several tools and work techniques such as flowcharts, use cases and activity diagrams. The programming language used in designing and implementing the system is PHP and the database used is MySql. The results of the study obtained that with the existence of this Application information system can facilitate village staff for the Process of Filling Death Forms, Births, coming and moving can be done quickly and efficiently.